(untitled) (Critical Journal of Social Sciences, 2026)
This research posits that enhancing the competitiveness of Egyptian universities is crucial for their integration into the global academic landscape. The study analyzes the significant challenges these institutions face and proposes actionable strategies to address them. By reviewing existing literature, academic papers, and relevant reports, the research situates its findings within both global and national contexts, with a specific focus on the Egyptian higher education system. A comprehensive examination of strategic plans and policies reveals key determinants of competitiveness, including research output, infrastructure development, student satisfaction, and employability. Additionally, the potential benefits of international collaborations are explored, underscoring their importance in enhancing university performance. Although the study does not include primary data collection, it provides valuable insights into the complexities of the Egyptian higher education landscape. The findings culminate in evidence-based recommendations for policymakers, university administrators, and stakeholders. By adopting these strategies, stakeholders can significantly improve the competitiveness of Egyptian universities, fostering their growth and enhancing their contributions to the international academic community.